2016
DOI: 10.1017/ice.2015.313
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Rapid Diagnostics and Antimicrobial Stewardship in Two Community Hospitals Improved Process Measures and Antibiotic Adjustment Time

Abstract: objective. To assess the impact of Matrix-Assisted Laser Desorption/Ionization Time-of-Flight (MALDI-TOF) mass spectrometry for rapid pathogen identification directly from early-positive blood cultures coupled with an antimicrobial stewardship program (ASP) in two community hospitals. Process measures and outcomes prior and after implementation of MALDI-TOF/ASP were evaluated.design. Multicenter retrospective study.setting. Two community hospitals in a system setting, Houston Methodist (HM) Sugar Land Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 21 publications
3
58
2
2
Order By: Relevance
“…Two studies have published theoretical applications of using BC‐GN testing in combination with local antibiograms to encourage less use of broad‐spectrum gram‐negative antibiotics . Other studies have shown decreased time to targeted antimicrobial therapy, but these did not include specific data on antibiotic utilization . A study conducted in Japan examining the impact of the gram‐negative and gram‐positive panels for community‐onset bacteremia reported a “common pattern” of de‐escalation among 12 patients with gram‐negative bacteremia from AP to non‐AP antibiotics (10 episodes of E. coli and 2 episodes of K. pneumoniae ) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies have published theoretical applications of using BC‐GN testing in combination with local antibiograms to encourage less use of broad‐spectrum gram‐negative antibiotics . Other studies have shown decreased time to targeted antimicrobial therapy, but these did not include specific data on antibiotic utilization . A study conducted in Japan examining the impact of the gram‐negative and gram‐positive panels for community‐onset bacteremia reported a “common pattern” of de‐escalation among 12 patients with gram‐negative bacteremia from AP to non‐AP antibiotics (10 episodes of E. coli and 2 episodes of K. pneumoniae ) .…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Other studies have shown decreased time to targeted antimicrobial therapy, but these did not include specific data on antibiotic utilization. 2,6,13 A study conducted in Japan examining the impact of the gram-negative and gram-positive panels for community-onset bacteremia reported a "common pattern" of de-escalation among 12 patients with gram-negative bacteremia from AP to non-AP antibiotics (10 episodes of E. coli and 2 episodes of K. pneumoniae). 14 The value of rapid multiplex polymerase chain reaction (PCR) for bacteremia was assessed in a study conducted at Mayo Clinic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that rapid identification of an organism by MALDI-TOF can improve time to appropriate antibiotic treatment, but only when associated with ASP collaboration. [16][17][18][19] The laboratory at WFBH implemented MALDI-TOF technology in 2014 and our AS team has been fundamental in educating providers on how to use the early identification result to implement empiric therapy by providing reliable local antibiogram reports. Overall at our institution, the implementation of MALDI-TOF has clearly improved turnaround time for identification of organisms.…”
Section: Matrix-assisted Laser Desorption/ionization Time-of-flight Tmentioning
confidence: 99%
“…[5][6][7][8][9] A collateral benefit to improved antimicrobial use in the inpatient setting is limiting antimicrobial expenditures. [10][11][12][13][14] For example, Standiford and colleagues 15 demonstrated that implementation of a robust ASP in a large, tertiary academic medical center resulted in a 46% reduction in antimicrobial cost per 1,000 patient-days. However, maintenance of such programs is key as there was a 32% cost increase within 2 years of discontinuation of the program.…”
mentioning
confidence: 99%